Prenatal Pollutant Exposures and Hypothalamic Development: Early Life Disruption of Metabolic Programming - Koshko, Lisa; Scofield, Sydney; Mor, Gil; Sadagurski, Marianna (Frontiers in Endocrinology, 2022)
Environmental contaminants in ambient air pollution pose a serious risk to long-term metabolic health. Strong evidence shows that prenatal exposure to pollutants can significantly increase the risk of Type II Diabetes (T2DM) in children and all ethnicities, even without the prevalence of obesity. The central nervous system (CNS) is critical in regulating whole-body metabolism. Within the CNS, the hypothalamus lies at the intersection of the neuroendocrine and autonomic systems and is primarily responsible for the regulation of energy homeostasis and satiety signals. The hypothalamus is particularly sensitive to insults during early neurodevelopmental periods and may be susceptible to alterations in the formation of neural metabolic circuitry. Although the precise molecular mechanism is not yet defined, alterations in hypothalamic developmental circuits may represent a leading cause of impaired metabolic reprogramming. In this review, we present the current knowledge on the links between prenatal pollutant exposure and the hypothalamic programming of metabolism.